Conference Proceedings. Assessing Language and (Inter) cultural Competences in Higher Education. Evaluation des compétences langagières et (inter) culturelles dans l’enseignement supérieur - Dervin, Fred & Suomela-Salmi, Eija (eds.) (fi=Turun yliopisto|en=University of Turku|, 2010)
This epublication contains papers that were presented at the conference “Assessing Language and (Inter) cultural Competences in Higher Education” which took place at the University of Turku (Finland) on 30.8.1.9.2007. The online proceedings may be downloaded and used provided the source is acknowledged.

Cet ouvrage rassemble certaines communications présentées à la conference « Evaluation des compétences langagières et (inter) culturelles dans l’enseignement supérieur » qui s’est tenue à l’Université de Turku (Finlande), les 30.8.1.9.2007. Vous pouvez télécharger les communications et les utiliser en mentionnant la source.